Development of E-Module Research and Development Materials for History Education Students - Kristoforus Bagas Romualdi; Andang Firmansyah; Michael Silvester Mitchel Vinco; Sunarto Sunarto (Indonesian Journal of Social Science Education (IJSSE), 2025)
The transformation of 21st century education requires history education students to master research and development (R&D) methods to create learning innovations. This research aims to develop e-module on research and development (R&D) materials that can be accessed through digital devices to answer these challenges. The research and development method with the ADDIE model is applied in five systematic stages. The results of validation by the first expert showed that the e-module was very feasible in the learning aspect (score 4.4), feasible in the content aspect (score 4.0) and very feasible for the media aspect (score 4.75). Then the second expert gave feasible on the learning aspect (score 3.4), very feasible on the content aspect (score 4.38) and feasible for the media aspect (score 3.5). User trials reinforced the findings with very feasible scores on all aspects: learning (4.63), content (4.48), and media (4.63). The findings prove that the developed e-module are feasible to use as learning media. This product has the potential to be an alternative digital-based learning media to support the mastery of R&D material in history education lectures.